Penggunaan Media Pembelajaran Bahasa Arab di MI Diponegoro - Rosyadi, Egadia Sabilar; Nabila, Syafira Azza; Alfia, Nurul (Prosiding Konferensi Nasional Bahasa Arab, 2023)
Utilizing appropriate learning media can capture students' interest in the learning process,fostering increased activity, affectivity, and creativity. This research aims to assess the utilizationof MI Diponegoro Arabic language learning media for grades 1–6, employing a qualitativeapproach based on field observations and interviews. The research findings indicate that theapplication of Arabic language learning media at MI Diponegoro appears to be somewhatmonotonous. In general, non-digital media is predominantly used, with only the upper classesincorporating digital media. This is attributed to limited teacher facilities and a restrictedunderstanding of media creativity.